Infectious Aerosol Capture Mask as Environmental Control to Reduce Spread of Respiratory Viral Particles - Joshua L. Santarpia; Nicholas W. Markin; Vicki L. Herrera; Daniel N. Ackerman; Danielle N. Rivera; Gabriel A. Lucero; Steven J. Lisco (Viruses, 2022)
Negative pressure isolation of COVID-19 patients is critical to limiting the nosocomial transmission of SARS-CoV-2; however, airborne isolation rooms are limited. Alternatives to traditional isolation procedures are needed. The evaluation of an Infectious Aerosol Capture Mask (IACM) that is designed to augment the respiratory isolation of COVID-19 patients is described. Efficacy in capturing exhaled breath aerosols was evaluated using laboratory experimentation, computational fluid dynamics (CFD) and measurements of exhaled breath from COVID-19 patients and their surroundings. Laboratory aerosol experiments indicated that the mask captured at least 99% of particles. Simulations of breathing and speaking showed that all particles between 0.1 and 20 µm were captured either on the surface of the mask or in the filter. During coughing, no more than 13% of the smallest particles escaped the mask, while the remaining particles collected on the surfaces or filter. The total exhaled virus concentrations of COVID-positive patients showed a range from undetectable to 1.1 × 106 RNA copies/h of SARS-CoV-2, and no SARS-CoV-2 aerosol was detected in the samples collected that were adjacent to the patient when the mask was being worn. These data indicate that the IACM is useful for containing the exhaled aerosol of infected individuals and can be used to quantify the viral aerosol production rates during respiratory activities.